COMPARISON OF PASSENGER CAR EQUIVALENT (PCE) VALUE IN MKJI 1997 AND PCE IN FIELD USING LINEAR REGRESSION METHOD IN (JENDRAL AHMAD YANI AND ADI SUCIPTO) ROAD BANYUWANGI CITY - Afifah Izza Farisa; Akhmad Hasanuddin; Anita Trisiana (Jurnal Rekayasa Sipil dan Lingkungan, 2020)
Passenger Car Equivalent (PCE) is a conversion rate that can be used to convert the unit of any variety of vehicles to be Passenger Car Unit (PCU). The PCE value on MKJI (Indonesian Highway Capacity Manual) is considered having a longer time span compared with what we own today, therefore the renewal of the PCE value is needed. Moreover, it deals with the differ characteristics of each area. The aim of this research is to get PCE value on Jendral Ahmad Yani (4/2 UD) and Adi Sucipto (4/2 D) roads in Banyuwangi District. The method used of this research is multiple linear regression. The obtained PCE value in this research on the right road of Adi Sucipto (heading to Jendral Ahmad Yani) are MC 0.125 and HV 4.350. While on the left road of Adi Sucipto (heading to S. Parman), the obtained PCE values are MC 0.293 and HV 3.212. Then, the obtained PCE values on Jendral Ahmad Yani are MC 0.248 and HV 3.4477. Ekivalensi Mobil Penumpang (EMP) merupakan angka konversi yang berfungsi untuk mengubah satuan dari macam-macam kendaraan menjadi Satuan Mobil Penumpang (SMP). Nilai EMP yang ada pada MKJI mempunyai rentan waktu yang lama dengan sekarang, untuk itu perlu adanya pembaruan nilai EMP dan ruas jalan yang ada setiap daerah mempunyai karakteristik yang berbeda. Tujuan dilakukannya penelitian ini adalah untuk mendapatkan nilai EMP pada ruas jalan Jendral Ahmad Yani (4/2 UD) dan Adi Sucipto (4/2 D) Kota Banyuwangi. Metode yang digunakan dalam penelitian ini adalah metode regresi linier berganda. Nilai EMP yang didapat pada penelitian ini untuk jalan Adi Sucipto kanan (arah Jendral Ahmad Yani) adalah MC 0,125 dan HV 4,350. Sementara nilai EMP yang didapat pada Jalan Adi Sucipto kiri (arah S. Parman) adalah MC 0,293 dan HV 3,212. Nilai EMP yang didapat pada Jalan Jendral Ahmad Yani MC 0,248 dan HV 3,447.